(untitled) (Bangladesh Journal of Endosurgery, 2014)
Retroperitoneal cysts (RCs) are rare. They are composed of both epithelial and mesothelial tissues, and those without an epithelial lining in the wall are called pseudocysts. Most retroperitoneal pseudocysts are pancreatic in origin, and nonpancreatic pseudocysts are very rarely reported.We report a case of large cystic lesion adjacent to the left kidney in a 25 years old man. He presented with 2 and half years history of gradual swelling of left upper abdomen. Abdominal ultrasonography and CT scan showed a large unilocular cystic mass in left side of the abdomen, which was attached with the lower pole of the left kidney. The cystic mass was excised laparoscopically. Histology showed a fibrous wall without epithelial lining thus confirming the diagnosis of a nonpancreatic pseudocyst.